2007
DOI: 10.1002/bit.21520
|View full text |Cite
|
Sign up to set email alerts
|

Structures of ionic liquids dictate the conversion and selectivity of enzymatic glycerolysis: Theoretical characterization by COSMO‐RS

Abstract: Lipase-catalyzed glycerolysis of triolein has been examined using a group of tetraammonium-based ionic liquids (ILs) as media, specifically with functional groups in cation part. The results demonstrated that the reaction evolution and profile specificity of respective IL system could be quantitatively associated with the structural characteristics of the IL by means of quantum chemical and COSMO-RS calculation. Misfit interaction, Van der Waals interaction and chemical potential, etc. derived from COSMO-RS ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 40 publications
1
42
0
Order By: Relevance
“…4 4 ] than in PF 6 − and BF 4 − based ILs. Xu and co-workers 183,185 utilized the conductorlike screening model for real solvents (COSMS-RS) to derive various parameters (such as misfit, H-bonding and van der Waals interaction energy) to understand the multiple interactions in ILs; the model also provides guidance in designing the structures of cations and anions. 190 The Kragl group 191 found that an IL in the Ammoeng family -Ammoeng 110 ( Fig.…”
Section: Manipulation/design Of Il Structuresmentioning
confidence: 99%
“…4 4 ] than in PF 6 − and BF 4 − based ILs. Xu and co-workers 183,185 utilized the conductorlike screening model for real solvents (COSMS-RS) to derive various parameters (such as misfit, H-bonding and van der Waals interaction energy) to understand the multiple interactions in ILs; the model also provides guidance in designing the structures of cations and anions. 190 The Kragl group 191 found that an IL in the Ammoeng family -Ammoeng 110 ( Fig.…”
Section: Manipulation/design Of Il Structuresmentioning
confidence: 99%
“…However, those descriptions could not or at least have not been associated with the quantification of the thermodynamic properties of ILs, which is just the need for a practical application 26 . (Fig.…”
Section: Analysis Of the Multiple Solvation Interactions Between Escumentioning
confidence: 99%
“…The ionic nature of ILs to strip of the essential water for catalysis action of enzyme has been suggested to be responsible for the lower activity of lipases in IL environment; however, Candida antarctica lipase B is structurally unique that could bind the essential water for catalysis and consequently works well at low water activities. 35 …”
Section: Resultsmentioning
confidence: 99%
“…For a multistep reaction, examination of the changes of activity coefficients of intermediate and end products in different biphasic systems with reaction evolution might be a good start to probe into the intrinsic reasons accounting for respective reaction specificity. 35 To simplify the simulation of the reaction progress, the following assumptions are established based on the observed characteristics of representative IL reaction system for enzymatic production of biodiesel (typically as in Ammoeng 102; Figure 1A): (1) this prediction is based on 1 mol triolein reacted with 3 mol methanol using 1 mol IL as a medium; (2) this work focuses on the partition coefficients of the end products (glycerol and biodiesel), all other components treated as part (composition) of two phases; (3) the formation of intermediate products (MG and DG) are treated as a steady state that the accumulation of MG and DG is neglected; (4) regarding the mutual solubilities of solvents, oil (TG and/or biodiesel, changing with reaction evolution) concentrations in ILs are estimated by COSMO-RS calculation at an infinite mode; and the solubilities of methanol, glycerol, and ILs in oil phase are omitted; (5) the volumes of oil phase (TG and biodiesel) and IL phase (IL, TG, biodiesel, methanol, and glycerol) are the sum of volume contributions from the compositions. Partition coefficients of biodiesel and glycerol in oil and IL phases (Ammoeng 102 and 120) are thus calculated on the basis of the above assumptions (Figure 2A).…”
Section: Partition Equilibrium and Reaction Specificitymentioning
confidence: 99%
See 1 more Smart Citation